2020
DOI: 10.1136/ijgc-2019-000923
|View full text |Cite
|
Sign up to set email alerts
|

Technetium-99m-indocyanine green versus technetium-99m-methylene blue for sentinel lymph node biopsy in early-stage endometrial cancer

Abstract: IntroductionThe low accuracy of pre-operative imaging techniques for prediction of nodal status strengthens the relevance of sentinel lymph node (SLN) biopsy in endometrial cancer, although the optimal method for its detection is still under investigation. The increasing use of indocyanine green (ICG) has aroused concern about its enhanced visualization of lymphatic channels, which could lead to a specimen that is thought to be nodal tissue not subsequently yielding a lymph node on pathologic analysis ('empty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
0
11
0
4
Order By: Relevance
“…Kessous et al (15) reported higher unilateral and bilateral SLN detection rates of 97.5% and 81.3%, respectively, with concomitant use of ICG and Tc99m-FSC. Recently, Cabrera et al (16) demonstrated significantly higher bilateral detection rate among patients injected with Tc-99m and ICG patients (69%). Our data agrees, highlighting the superiority of Tc99m-ICG combination over Tc99m-FSC alone for bilateral detection (87.3% vs. 63.4%, p=0.0006).…”
Section: Discussionmentioning
confidence: 96%
“…Kessous et al (15) reported higher unilateral and bilateral SLN detection rates of 97.5% and 81.3%, respectively, with concomitant use of ICG and Tc99m-FSC. Recently, Cabrera et al (16) demonstrated significantly higher bilateral detection rate among patients injected with Tc-99m and ICG patients (69%). Our data agrees, highlighting the superiority of Tc99m-ICG combination over Tc99m-FSC alone for bilateral detection (87.3% vs. 63.4%, p=0.0006).…”
Section: Discussionmentioning
confidence: 96%
“…A combination of ICG with Tc99m nanocolloid to show and detect sentinel lymph nodes in patients with endometrial cancer has recently come into the focus of scientific interest. Kessous et al reported in their study of 157 patients with endometrial cancer that a triple tracer combination (ICG, Tc99m and patent blue) does not lead to a significant improvement in the overall detection rate (93.5 vs. 97.5 %) and bilateral detection rate (80.5 vs. 81.3 %) compared with a double tracer combination (ICG and ▶ Table 2 Sentinel lymph node detection rates: overall and bilateral detection rates (modified and supplemented from [11] [43]. As regards the overall detection rate (93 vs. 94 %) there was no significant difference between the 2 groups, but the bilateral detection rate was significantly higher (69 vs. 41 %) in the patients who had mapping by means of a combination of ICG and Tc99m [43].…”
Section: Technical Aspects Of Sentinel Lymph Node Biopsy: Injection Site and Methodsmentioning
confidence: 99%
“…Kessous et al reported in their study of 157 patients with endometrial cancer that a triple tracer combination (ICG, Tc99m and patent blue) does not lead to a significant improvement in the overall detection rate (93.5 vs. 97.5%) and bilateral detection rate (80.5 vs. 81.3%) compared with a double tracer combination (ICG and Tc99m) 42 . In a group of 84 patients with endometrial cancer Cabrera et al compared the sentinel lymph node detection rate after mapping by a combination of ICG and Tc99m (35 patients) to mapping with the combination of ICG and methylene blue (49 patients) 43 . As regards the overall detection rate (93 vs. 94%) there was no significant difference between the 2 groups, but the bilateral detection rate was significantly higher (69 vs. 41%) in the patients who had mapping by means of a combination of ICG and Tc99m 43 .…”
Section: Technical Aspects Of Sentinel Lymph Node Biopsy: Which Tracer/which Dye?mentioning
confidence: 99%
See 2 more Smart Citations